APPROACH TO MICROTEXTS AS A SPEECH SYSTEM (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the theoretical foundations of approaching microtexts as speech systems within the broader framework of text linguistics. The study argues that a microtext constitutes an integral communicative system whose internal elements are interconnected through semantic, syntactic, and stylistic relations. At the same time, a microtext functions as a structural component of a macrotext and contributes to the formation of textual coherence and integrity. Drawing on the principles of systems theory and text linguistics, the research analyzes the relationships among linguistic units operating within microtexts and demonstrates how these units acquire new semantic and functional qualities in context. Through the examination of literary and journalistic texts, the study reveals that microtexts are not merely collections of sentences but organized communicative structures characterized by internal cohesion, semantic unity, and systemic interdependence. The findings support the view that microtexts should be regarded as independent speech systems while simultaneously functioning as constituent elements of larger textual formations.
Keywords: Text, the category of text, dominant structures in text formation, system, system speech, integrity, cohesion, coherence, speech occurence, macrotext, expressive means, imagery, spiritual expression, cause and effect relations, phoneme, lexeme, phraseme, syntaxeme, content in microtext, morpheme, context, word choice, microtext, meaning shadowing, sense modality.